Neuronal Dysfunction Is Linked to the Famine-Associated Risk of Proliferative Retinopathy in Patients With Type 2 Diabetes - Fedotkina, Olena; Jain, Ruchi; Prasad, Rashmi B.; Luk, Andrea; García-Ramírez, Marta; Özgümüs, Türküler; Cherviakova, Liubov; Khalimon, Nadiya; Svietleisha, Tetiana; Buldenko, Tetiana; Kravchenko, Victor; Jain, Deepak; et al. (Frontiers in Neuroscience, 2022)
Persons with type 2 diabetes born in the regions of famine exposures have disproportionally elevated risk of vision-threatening proliferative diabetic retinopathy (PDR) in adulthood. However, the underlying mechanisms are not known. In the present study, we aimed to investigate plausible molecular factors underlying progression to PDR. To study the association of genetic variants with PDR under intrauterine famine exposure, we analyzed SNPs that were previously reported to be associated with 2 diabetes, glucose, and pharmacogenetics. Analyses were performed in the population from northern Ukraine with the history of exposure to the Great Ukrainian Holodomor famine (the DOLCE study, n=3,583) and validated top genetic findings in the Honk Kong Diabetes registry (HKDR, n=730). In DOLCE, genetic risk for PDR was elevated for variants in ADRA2A, PCSK9, and CYP2C19*2 loci, but reduced at PROX1 locus. Association of ADRA2A loci with risk of PDR in famine-exposed group was further replicated in HKDR. Exposure of embryonic retinal cells to glucose starvation, mimicking the perinatal exposure to famine, resulted in sustained increased expression of Adra2a and Pcsk9, but decreased Prox1. Exposure to starvation exhibited a lasting inhibitory effects on neurite outgrowth, as determined by neurite length. In conclusion, consistent genetic findings on famine-linked risk of ADRA2A with PDR indicate that nerves may likely to be responsible for communicating the effects of perinatal exposure to famine on the elevated risk of PDR in adults. These results suggest the possibility of utilizing neuroprotective drugs for the prevention and treatment of PDR.